Static and fatigue failure analysis of adhesively bonded thick composite single lap joints - Tang, J. H. (2014)
Static and fatigue behavior of thick composite laminate single lap joints with thick adhesive bondline is experimentally and numerically investigated. Stress based analysis is used to understand the uniaxial tensile behavior of thick glass fiber reinforced epoxy laminates bonded with relatively thick epoxy adhesive. The effect of adhesive thickness on relatively thick adherend on the fatigue initiation life was modeled with generalized stress singularity approach. It was observed that the failure onset always occurred at adherend–adhesive interface. Subsequent crack propagation mostly resulted in interlaminar failure of adjacent first angle ply near to this interface. Both static and fatigue strength values decrease with increase of bondline thickness. Evaluation of generalized stress intensity factors of the corner geometry (square edge joint) provided a good correlation between predictions and experimental measurements.